Rational models of acceleration of multi-purple abrasive circuit with planitary drive - Ben І.О. (Forestry, Forest, Paper and Woodworking Industry, 2018)
The sharpening feature of peeling and pruning knives is that they have a wide back surface, small sharpening angles and a large length. The large contact area of ​​the abrasive wheel with the blade surface causes high temperatures to form on the blade surface. As a result, the initial properties of the blade change, its ignition occurs, there are large burrs, microcracks, chipping and other defects. The recommendations available for rational sharpening and fine-tuning of wood-cutting tools, in particular peeling and milling cutters, partially address this problem but significantly reduce the performance of the sharpening process. This problem is solved by the use of many cup abrasive wheels, which is an option for continuous grinding. It is established that the knife surface temperature is influenced by three main influencing factors: cutting speed in m / s; feed rate of the circle in m / min. ; feed circle on the cut in mm. But differences in the dimensions of influential factors do not allow to consider them in one coordinate system. It is suggested to translate the dimensions of influential factors into a normalized form and combine them into one coordinate system, determine the regression equation, investigate it for the extremum and find rational modes of exacerbation. It is shown that the dependences of the surface temperature of the knife on the cutting speed, the feed rate of the circle and the feed on the cutting have an exponential dependence and the dependence of the total knife temperature has a polynomial dependence. After equating this dependence to zero and differentiating, we obtained the value of the optimal value of the influencing factors in the normalized form = 0,3075757. After translating this value into rational form, rational cutting modes were obtained: cutting speed – 38,075757 m/s; feed rate of the circle – 9,2303028 m/min; feed circle for cutting – 0,137681813 mm. The introduction of these sharpening modes allows to reduce the surface temperature of the knife to 377,337 °C, to reduce the duration of sharpening, to increase the durability of the knife with respect to blunting, and thus to increase the productivity of the peeling machine.